Physical activity across days of week, video games, and laptop use are more likely to influence weight gain among Saudi Youth - Alibrahim, Mohammed Shaab (Frontiers in Sports and Active Living, 2022)
Purpose The purpose of this study was to determine the extent and prevalence of daily PA and the sedentary behavior during inactive spare-time among young Saudis and their effect on overweight and obesity. Methods A total of 357 students completed all stages of this study. They included 282 boys aged 11.95 ± 0.73 years (213 children aged 11.62 ± 0.506 years and 69 adolescents aged 13.16 ± 0.373 years) and 75 girls (16 children aged 11.94 ± 0.236 years and 59 adolescents aged 13.47 ± 0.626 years). For each participant, height and weight were measured, and BMI was calculated. A questionnaire asking about daily PA and sedentary habits during the previous 7 days was also used. Multiple comparisons were performed to test for differences between groups by sex and age category, and stepwise multiple regression analysis was used to determine which variables significantly affected BMI. Results The overall prevalence of overweight and obesity was 17.02 and 28.37% in boys and 9.33 and 0% in girls, respectively. The patterns of PA were changing within elements and between sexes. Both groups of boys were more active than girls during breakfast and lunch periods (p < 0.001 for all). A significant difference in favor of boys was also observed between the two groups of boys and the group of adolescent girls regarding after-school physical activity (p < 0.05 for all). Prepubescent boys reported being generally less active during the previous 7 days than their female counterparts and adolescent peers. Sedentary behaviors did not differ between all groups. Playing video games and using laptops were the parameters significantly associated with BMI. Conclusions This study noted that the prevalence of overweight and obesity was more pronounced in boys than in girls. However, boys were more active but had the same degree of sedentary behavior as girls. Physical activity across the days of weekly, video games, and laptop use were the parameters that most affected BMI.